Can the curriculum be used to estimate critical velocity in young competitive swimmers? - Costa, A. M.; Silva, A. J.; Louro, H.; Reis, V. M.; Garrido, N. D.; Marques, M. C.; Marinho, D. A. (Journal of Sports Science & Medicine, 2009)
The aims of the present study were to assess critical velocity using the swimmer curriculum in front crawl events and to compare critical velocity to the velocity corresponding to a 4 mmol·l-1 of blood lactate concentration and to the velocity of a 30 min test. The sample included 24 high level male swimmers ranged between 14 and 16 years old. For each subject the critical velocity, the velocity corresponding to a 4 mmol·l-1 of blood lactate concentration and the mean velocity of a 30 min test were determined. The critical velocity was also estimated by considering the best performance of a swimmer over several distances based on the swimmer curriculum. Critical velocity including 100, 200 and 400 m events was not different from the velocity of 4 mmol·l-1 of blood lactate concentration. Critical velocity including all the swimmer events was not different from the velocity of a 30 min test. The assessment of critical velocity based upon the swimmer curriculum would therefore seem to be a good approach to determine the aerobic ability of a swimmer. The selection of the events to be included in critical velocity assessment must be a main concern in the evaluation of the swimmer.